A biogas-fired cogeneration system based on chemically recuperated gas turbine cycle. (1st February 2020) - Su, Bosheng; Han, Wei; He, Hongzhou; Jin, Hongguang; Chen, Zhijie; Yang, Shaohui
Highlights: A new system based on chemically recuperated gas turbine cycle is proposed. Chemical and physical energy are used in a cascaded way. Much latent heat can be recovered due to the biogas reforming process. Application of the new design increases the power generation significantly. The energy grade matches better in the digester. Abstract: Efficient use of biogas has been increasingly important due to the increased scale of biogas plants all over the world. Conventional biogas-fired combined heat and power designs take full advantage of the physical energy in the exhausted gas from the power engine; however, the chemical energy in biogas destroys significantly in the combustion. A biogas-fired cogeneration system based on chemically recuperated gas turbine cycle may become a promising technology to make the best of both chemical and physical energy, and is therefore studied and discussed in this paper. By introducing a biogas steam reforming process, more electric power can be generated due to the higher chemical energy in syngas. In addition, the exhausted gas from the power engine is rich in moisture; thus, the large amount of the low-temperature heat may be recovered for the low-temperature heat demand in the digester. The comparative studies demonstrate that the new design, integrated with the well-established devices, relieves the local heat island effect and increases the power generation. Typical days analysis in four seasons were conducted to show the advantages of the new design. The applied thermal insulation material will affect the optimal steam to carbon molar ratio and also the economic performance in the system annual operation, which is considered in the future study. This paper should provide a new and efficient way to use biogas.